Re-Envisioning Global Health Competencies for the African Region Aligned with Local Health Needs and Resources - Ritika Tiwari; René English; Kerrin Begg; Usuf Chikte (Ubiquity Press, 2022)
Background: While many Global Health programs aim to address health inequalities within and between HICs and low- and middle-income countries (LMICs) there is a need to establish new Global Health academic programs within the growing trend towards 'internationalization of higher education'. Objective: This study was undertaken to re-envision Global Health competencies for the African region context with respect to the local health needs and availability of resources. Methods: This study was undertaken over a period of four years from 2017 till 2020. A three-pronged strategy was undertaken to scan, scope, distil and develop a set of Global Health domains and competencies for the African region. Strategy 1 encompassed an environmental scan of Global Health competencies (2017-2019), and a literature review (2017-2020); strategy 2 comprised a scoping of education programs in Global Health (2018-2019); and strategy 3 involved an interest-group discussion in a face-to-face conference. Findings: Seven core and four cross-cutting global health competency statements were developed for the African region. The core competency statements included following domains: global health systems and international relations; global evidence ecosystem; role of international organizations; universal health issues; intellectual property rights; responses to issues affecting different at-risk groups; local, national, and international policy and economic context affecting global health. The four cross-cutting competency statements included following domains: digital and academic literacies; quantitative and qualitative research; policy and funding allocation resources; ethical conduct of global health practice and research global health. Conclusion: There is a need to enable higher education institutions (HEIs) from the Global South to offer global health qualifications with a set of competencies that better approximate solutions to contextualised problems - not only to students from the Global South but also from the Global North. The global health competencies developed in this research study will enable African HEIs to offer global health education in a more pragmatic manner.